Implications of changing El Niño patterns for biological dynamicsin the equatorial Pacific Ocean - Turk, D.; Meinen, C.; Antoine, David; McPhaden, M.; Lewis, M. (American Geophysical Union, 2011)
El Niño events are known to strongly affect biological production and ecosystem structure in the tropical Pacific. Understanding and predicting biological processes in this area are hampered because the existing in situ observing system focuses primarily on physical measurements and does not observe key biological parameters; the only high spatial and temporal resolution biology-related observations are from the global array of ocean color satellites which provide an estimate of surface chlorophyll concentrations only. Since the1990s, an apparent shift of the El Niño maximum sea-surface temperature (SST) warm anomaly from the eastern to the central equatorial Pacific has frequently been observed. Satellite observations show significant changes in chlorophyll-a(Chl-a), new production (NP) and total primary production(PP) in the equatorial Pacific associated with these new central Pacific (CP) El Niño events (also called El Niño Modoki) relative to eastern Pacific El Niños. During CP-El Niños, NP, Chl-a and PP in the central basin are depressed relative to EP-El Niños and lower values of Chl-a and PP coincide spatially with higher SST in the central Pacific. While surface Chl-a, and integrated NP and PP over the entire equatorial band, decrease during both CP and EP-El Niños, the magnitude of this decrease seems to depend more on the intensity than type of event. The changing spatial patterns have significant implications for equatorial biological dynamics if, as has been suggested, CP-El Niños increase in frequency in the future.